2008
DOI: 10.1038/npp.2008.144
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 and Adenosine A2A Receptors Regulate NMDA-Mediated Excitation in Accumbens Neurons Through A2A–D2 Receptor Heteromerization

Abstract: Bursting activity of striatal medium spiny neurons results from membrane potential oscillations between a down- and an upstate that could be regulated by G-protein-coupled receptors. Among these, dopamine D2 and adenosine A2A receptors are highly enriched in striatal neurons and exhibit strong interactions whose physiological significance and molecular mechanisms remain partially unclear. More particularly, respective involvements of common intracellular signaling cascades and A2A–D2 receptor heteromerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 62 publications
(132 reference statements)
8
166
0
3
Order By: Relevance
“…We also show here that the A 2A receptor agonist, CGS21680, did not cause any pharmacological effect on the firing rate or pattern of dopamine neurons, confirming the lack of pharmacologically accessible A 2A receptors on dopamine neurons, which is in agreement with a low level of A 2A receptor expression in the VTA (Rosin et al, 1998;Rosin et al, 2003). CGS21680 also failed to acutely alter D 2 receptor function in the VTA, indicating a lack of direct pharmacological interaction between D 2 and A 2A receptors in the VTA, like those in the striatum (Azdad et al, 2009).…”
Section: Potency Of Quinpirole On Dopamine Neuron Firing Is Similar Bsupporting
confidence: 60%
See 1 more Smart Citation
“…We also show here that the A 2A receptor agonist, CGS21680, did not cause any pharmacological effect on the firing rate or pattern of dopamine neurons, confirming the lack of pharmacologically accessible A 2A receptors on dopamine neurons, which is in agreement with a low level of A 2A receptor expression in the VTA (Rosin et al, 1998;Rosin et al, 2003). CGS21680 also failed to acutely alter D 2 receptor function in the VTA, indicating a lack of direct pharmacological interaction between D 2 and A 2A receptors in the VTA, like those in the striatum (Azdad et al, 2009).…”
Section: Potency Of Quinpirole On Dopamine Neuron Firing Is Similar Bsupporting
confidence: 60%
“…Via different G-protein coupling and second messenger systems, the activation of the adenosine A 2A receptors increases cAMP levels and cellular excitability, while the activation of the dopamine D2 receptors decreases cAMP levels and cellular excitability. Antagonistic interactions between the two receptor systems are also manifested by direct receptor-receptor cross-talk in the form of heterodimers, where stimulation of the adenosine A 2A receptors causes a reduction in the affinity of dopamine D 2 receptor agonists and vice versa (Ferre et al, 1991;Kull et al, 1999;Azdad et al, 2009). The functional interactions between adenosine A 2A receptors and dopamine D 2 receptors are thought to underlie the involvement of adenosine A 2A receptors in the control of several behavioral functions (Sebastiao & Ribeiro, 1996;Fredholm et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been further suggested that an imbalance in adenosine signaling, a neurotransmitter which modulates both dopamine and glutamate transmission, may be a central factor in the susceptibility to develop schizophrenia (Boison et al, 2012). In support of this hypothesis, it has been repeatedly shown that enhancing NMDA receptor function improves the negative and cognitive symptoms of schizophrenia (Coyle, 2012), and interestingly, heteromerization of the D2R with the A2R negatively regulated D2R-induced suppression of NMDA-mediated depolarization plateau potential (Azdad et al, 2009).…”
Section: Adenosine-dopamine Receptor Heteromers: A1-d1 A2-d2mentioning
confidence: 60%
“…We showed previously that presynaptic and postsynaptic effects of A 2A receptor antagonists depend on the differential affinity of ligands for different A 2A receptor heteromers, which are differentially localized in different striatal neuronal elements. Thus, postsynaptic A 2A receptors are mostly localized in striatal medium spiny neurons (MSNs) that project to the external segment of the globus pallidus, in which they form heteromers with dopamine D 2 receptors, which modulate neuronal excitability (Azdad et al, 2009). Blockade of postsynaptic A 2A receptors mediates the locomotor activating effects of A 2A receptor antagonists and is also involved in the locomotor activating effects of the nonselective adenosine receptor antagonist caffeine (Ferré et al, 2008;Orru et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental chambers and other apparatus, as well as the general self-administration procedure, were as described previously (Justinová et al, 2003). Monkeys were surgically prepared with chronic indwelling venous catheters (polyvinyl chloride;Goldberg 1973). At the start of the session, a white house light was turned off, green stimulus lights were turned on, and monkeys were required to make 10 responses on a lever [10-response, fixed-ratio schedule of reinforcement (FR10)], which turned off the green lights and produced an intravenous injection of 4 g/kg THC (0.2 s, 0.2 ml) paired with a 2 s amber light.…”
Section: Methodsmentioning
confidence: 99%